Analytical Essays on Music by Women Composers: Secular and Sacred Music to 1900 – edited by Laurel Parsons and Brenda Ravenscroft (Book review) - Prevost, Roxane (CAML Review / Revue de l'ACBM, 2019)
[no abstract]